1996
DOI: 10.1159/000244286
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Tracheal Infusion of Surfactant versus Bolus Instillation in Rabbits: Effects on Oxygenation, Blood Pressure and Surfactant Distribution

Abstract: Surfactant bolus instillation may be associated with a drop in blood pressure. Platelet-activating factor (PAF) has been found in surfactant preparations. The aim of this study was to evaluate rapid tracheal infusion of surfactant during 5 min as an alternative to bolus instillation and to examine whether a PAF receptor antagonist is able to prevent the decrease in blood pressure. Methods: Surfactant deficiency was induced in 16 adult rabbits by lung lavages with saline. Six animals received a bolus of a porci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…Animal studies show that rapid boluses are necessary for optimal distribution of surfac- tant to the lungs and physiological effects [8] . To avoid intubation, attempts have been made to give surfactant by aerosolization, but the results did not show benefi cial effects [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies show that rapid boluses are necessary for optimal distribution of surfac- tant to the lungs and physiological effects [8] . To avoid intubation, attempts have been made to give surfactant by aerosolization, but the results did not show benefi cial effects [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Further there is a possibility that some of the surfactant components, lipids or proteins, induces a vasodilatation, either directly or by release of vasoactive substances. Moya et al demonstrated occurrence of platelet activating factor in Curosurf (21), but this finding was only partially confirmed by others, and was shown not to influence the haemodynamic response (22). A vasoactive agent should bind to endothelial receptors activating nitric oxide synthase (6).…”
Section: Discussionmentioning
confidence: 98%
“…Lung function data were not provided in that study. The same authors 34 compared bolus application vs. surfactant infusion over 5 min in the same rabbit model. Again, surfactant distribution in the lung was much less homogeneous in the animals belonging to the infusion group.…”
Section: Discussionmentioning
confidence: 99%